HIDROLISIS GELATIN TULANG IKAN KAKAP MENGGUNAKAN LARUTAN ASAM (The Hydrolysis Gelatin of Kakap Fish Bone Using Acid Solution) - Mulyani, Tri; HP, Sudaryati; Rahmawati, Siska F (UPN VETERAN JAWA TIMUR, 2011)
Gelatin is a natural product obtained by hydrolysis of collagen, a soluble protein, which acts as the gelling agent. In general, the process of making gelatin begins with soaking the bone in acid solution, aimed at dissolving calcium phosphat and other mineral salts. This treatment resulted in changes to the texture bone , so that bones become relatively non-rigid. Type of acid used is strong acids, namely HCl, H2SO4 and H3PO4, with the level of 3% - 6% concentration. The purpose of this study was to determine the type and concentration of acid as a soaking solution. The result showed that the best treatment was HCL concentration of 3%, with water content 6.54%, ash 3.27%, 77.92% protein, gel strength 72.07 bloom, viscosity 17.86 cp, pH 4.88 and yield 14.03%. Key words : gelatin, collagen, bone, hydrolysis